FRI0166 Vgamma 9/vdelta 2 t lymphocytes in italian patients with behÇet's disease. (1st June 2001) - Triolo, G; Accardo-Palumbo, A; Ferrante, A; Ciccia, F; Giardina, E; Licata, G
Abstract : Background: Behçet's disease (BD) is a multisystemic disorder with oral and genital ulcers, muco-cutaneous, ocular, joint, vascular and central nervous system involvement. Increases in gamma/delta T cells in peripheral blood and cerebrospinal fluid and gamma delta T cells responses to HSP-derived peptides suggest a role for this T cell subset in the aetiopathogenesis of BD. Objectives: To substantiate this hypothesis, we set out to shed light upon the characteristics of the gamma/delta T lymphocytes in Italian BD patients. The response of Vgamma9/Vdelta2 (Vg9/Vd2) cells to phosphoantigens in disease course was also investigated in vitro and compared to the response of normal controls. Methods: 25 BD patients and healthy subjects were studied. Peripheral blood mononuclear cells (PBMC) were obtained from each individual and specific cells analysed by FACS utilising specific monoclonal antibodies. For the expansion of Vg9/Vd2 T cells PBMC were cultured for 10 days in medium alone, or in the presence of phosphoantigens: xylose 1-P, ribose 1-P, Dimethylallyl pyrophosphate (DMAPP), Isopentenyl pyrophosphate (IPP). The Vd2 expansion factor (EF) was then calculated by diving the percentage of Vd2 T cells in phosphoantigen + IL-2-stimulated cultures by the percentage of Vd2 T cells obtained in cultures containing IL-2 only. The expression of TNF-RII and IL-12Rb1 on Vg9/Vd2 was evalued by the simultaneous use of anti-TNF-R II-PE or anti-IL-12Rb1-PE and anti-Vd2TCR FITC. The expression of these receptor after in vitro stimulation with phosphoantigens was also studied. Results: There were no statistical differences in percentage of Vd2 T cells between patients with active (2, 63 ± 1, 73%) and inactive (2, 02 ± 1, 26%) disease. There was a certain hierarchy in the response of Vg9/Vd2 cells toward the different phosphoantigens, with the highest EF obtained with DMAPP, the lowest obtained with xyl-1P. Specifically the EF of Vd2 cells of patients with BD was 4 fold highest than that detected in healthy controls (EF = 113, 4 ± 153 and 28, 5 ± 22.5 respectively); in addition the EF of Vd2 in PBMC from patients with active disease was 5 fold highest than that of the cells from patients with inactive disease (EF = 170 ± 180 and 34, 1 ± 30, 6 respectively). TNF-RII and IL-12-Rb1 expression were increased after 10 day cultures in both patient groups and in normal controls. The proportion of Vg9/Vd2 bearing these receptors was raised in active patients (17.7 ± 1 and 49.2 ± 5.55 respectively), when Vd2 cell population were cultured in presence of DMAPP. Conclusion: Our observations indicate that Vd2 activation is correlated with BD progression. It is of interest the involvement of Vd2 lymphocytes in active disease and the absence of response to phosphoantigens in vitro in patients in complete remission. Further definition and effector functions of the Vg9/Vd2 cells are required to improve their role in the maintenance of activity disease. In addition, the inhibition of gd activation and therefore of the pro-inflammatory CK production may provide an interesting therapeutic strategy for the novel treatments for BD